2016
DOI: 10.1128/aem.03174-15
|View full text |Cite
|
Sign up to set email alerts
|

Bromochloromethane, a Methane Analogue, Affects the Microbiota and Metabolic Profiles of the Rat Gastrointestinal Tract

Abstract: Bromochloromethane (BCM), an inhibitor of methanogenesis, has been used in animal production. However, little is known about its impact on the intestinal microbiota and metabolic patterns. The present study aimed to investigate the effect of BCM on the colonic bacterial community and metabolism by establishing a Wistar rat model. Twenty male Wistar rats were randomly divided into two groups (control and treated with BCM) and raised for 6 weeks. Bacterial fermentation products in the cecum were determined, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 61 publications
1
12
0
1
Order By: Relevance
“…Gordon et al [21] revealed that the co-inoculation of gnotobiotic mice with M. smithii and the polysaccharidefermenting bacterium B. thetaiotaomicron significantly increased the amounts of caecal fermentation products (such as acetate, propionate and butyrate), total liver triglycerides and host fat stores without affecting the total BW. Several previous studies showed that antimethanogenic compounds (such as bromochloromethane) could effectively decrease the abundance of methanogen populations and have no effect on BW [89,90]. In addition, our results demonstrated that Methanobrevibacter had limited association with other gut microbiota and was not influenced by host genetic regulation.…”
Section: Discussionsupporting
confidence: 48%
“…Gordon et al [21] revealed that the co-inoculation of gnotobiotic mice with M. smithii and the polysaccharidefermenting bacterium B. thetaiotaomicron significantly increased the amounts of caecal fermentation products (such as acetate, propionate and butyrate), total liver triglycerides and host fat stores without affecting the total BW. Several previous studies showed that antimethanogenic compounds (such as bromochloromethane) could effectively decrease the abundance of methanogen populations and have no effect on BW [89,90]. In addition, our results demonstrated that Methanobrevibacter had limited association with other gut microbiota and was not influenced by host genetic regulation.…”
Section: Discussionsupporting
confidence: 48%
“…In mice, the presence of methanogens led to a more efficient carbohydrate digestion and higher body fat stores (but not higher BM) at similar food intakes, compared to animals without methanogens or those inoculated with a sulphate-reducing bacterium as an alternative H 2 sink (Samuel and Gordon, 2006). In rats, reducing methanogens led to a less efficient use of carbohydrates, but no change in BM over 6 weeks (Yang et al, 2016). Reducing methanogens/CH 4 emissions in humans has been associated with a decrease in digesta retention (Ghoshal et al, 2018).…”
Section: Why Harbour Methanogens?mentioning
confidence: 89%
“…Soil DNA Kit (Omega Bio-tek, Norcross, GA, United States) according to manufacturer’s protocols. The final DNA concentration and purity were determined by NanoDrop 2000 UV–vis spectrophotometer (Thermo Scientific, Wilmington, NC, United States), and DNA quality was checked by 1% agarose gel electrophoresis ( Yang et al, 2015 ). The V3–V4 hypervariable regions of the bacterial 16S rRNA gene were amplified with primers 338F (5′-ACTCCTACGGGAGGCAGCAG-3′) and 806R (5′-GGACTACHVGGGTWTCTAAT-3′) by PCR (GeneAmp 9700, ABI, United States; Singh et al, 2015 ) using the following program: 3 min denaturation at 95°C; 27 cycles of 30 s at 95°C, 30 s annealing at 55°C, and 45 s elongation at 72°C; and a final extension at 72°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%